Follicular fluid-derived small extracellular vesicles during individual in vitro maturation improve blastocyst development - Azari-Dolatabad, Nima; Eshghi, Davoud; Benedetti, Camilla; Fernandez Montoro, Andrea; Xie, Lei; Le Graffric Molto, Fabiola; Moorey, Sarah E.; Hendrix, An; Opsomer, Geert; Leroy, Jo L. M. R.; Van Soom, Ann; Chaitanya Pavani, Krishna; et al. (Frontiers in Veterinary Science, 2025)
IntroductionWe evaluated the impact of follicular fluid-derived small extracellular vesicles (FF-sEVs) supplementation during oocyte maturation in vitro on bovine embryo outcomes, comparing group and individual culture systems.MethodsFollicular fluid was aspirated from dominant follicles of four nulliparous Holstein heifers at 4.5 days post-ovulation. Small extracellular vesicles were isolated, characterized, and pooled to ensure balanced donor contribution. To confirm uptake, FF-sEVs were fluorescently labelled and co-cultured with cumulus-oocyte complexes (COCs) during in vitro maturation. Fluorescent labelling confirmed FF-sEVs internalization by oocytes and granulosa cells. Next, COCs were matured in vitro with FF-sEVs at varying concentrations (group system: 0, 5, 10, 25, 50 μg/mL; individual system: 0, 6.5, 12.5, 25 μg/mL), fertilized, and cultured. Blastocyst quality was assessed via differential-apoptotic staining.ResultsIn group culture, the control group exhibited higher day 8 blastocyst rates compared to 10, 25, and 50 μg/mL FF-sEVs groups, while 5 μg/mL FF-sEVs showed no difference. Blastocysts developed from oocytes matured in 25 and 50 μg/mL groups had reduced total cell numbers versus controls and groups matured in lower FF-sEVs concentrations. Conversely, individual maturation with 6.5 μg/mL FF-sEVs enhanced day 8 blastocyst rate, total cell counts, inner cell mass, and reduced apoptotic ratios compared to all other groups.Discussion and conclusionWe propose that intercellular communication in group cultures, potentially mediated by endogenous embryotropins (including sEVs), may mask FF-sEVs benefits. In individual systems, where such interactions are absent (or minimal), FF-sEVs significantly improved embryo competence. These findings underscore FF-sEVs as a promising tool to refine assisted reproductive technologies, contingent on culture conditions.